ANALISIS KINERJA KEUANGAN DEBITUR INTI BANK ABC DENGAN MENGGUNAKAN ANALISA Z-SCORE - Windy Wijaya Kesuma; Suhartono Suhartono (Universitas Lambung Mangkurat, 2013)
This present study purposed to know the result from applied of Altman Z-Score Analysis (Second Model) for Financialperformance analysis of prime credit customer ABC Bank. And also to knowing that analysis method can be used in credit analysis process of ABC Bank expecially for early warning system in financial condition of credit customer. This research using seven prime credit customer ABC Bank for sample and the result of this study shows that almost all prime credit customer in the sample predicted will be bancrupcy (grey area and distrees area) at first lending conditions and financial review conditions. The result of this research is obtained the fact than Altman Z-Score Analysis can be used as the one of analysis tools in the credit analysis process at ABC Bank. Z-Score Analysis can be giving the information about real financial condition of prime credit customer than the information will be advising for board of management ABC Bank to increasing the quality of credit analysis their Credit Officer.